2019
DOI: 10.1039/c9fo00638a
|View full text |Cite
|
Sign up to set email alerts
|

Modulating effects of polysaccharides from the fruits ofLycium barbarumon the immune response and gut microbiota in cyclophosphamide-treated mice

Abstract: The effects were investigated of Lycium barbarum polysaccharides on immunoregulation and gut microbiota dysbiosis in CTX-induced mice to elucidate whether the attenuation of immunosuppression is related to the modulation of the gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
129
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 40 publications
9
129
0
Order By: Relevance
“…A recent study indicated that an imbalance of immune function was closely related to dysbiosis of the intestinal microbiota [3], as the gut barrier was disrupted and digestive system complications developed in the immunocompromised group [4]. The commensal microbiota plays an important role in the development and maintenance of the immune system and intestinal homeostasis via stimulating the immune response and maintaining the epithelial barrier functions [5]. Hence, gut microbiota dysbiosis is closely related to immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study indicated that an imbalance of immune function was closely related to dysbiosis of the intestinal microbiota [3], as the gut barrier was disrupted and digestive system complications developed in the immunocompromised group [4]. The commensal microbiota plays an important role in the development and maintenance of the immune system and intestinal homeostasis via stimulating the immune response and maintaining the epithelial barrier functions [5]. Hence, gut microbiota dysbiosis is closely related to immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, gut microbiota dysbiosis is closely related to immunosuppression. For example, cyclophosphamide-induced immunosuppressed mice exhibited a decrease in the richness of bacterial species and an increase in the proportion of Bacteroidetes, while the proportion of Firmicutes and Proteobacteria increased [1,3,5]. This suggests that an imbalance of the immune system causes dysbiosis of the intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that TFPS could increase probiotic Lactobacillus and reduce risk Akkermansia , to maintain or improve the gut health. It was also found that polysaccharides form Lycium barbarum were capable of increasing the abundance of Lactobacillus (Ding et al., 2019). The common characteristic of these polysaccharides is that they are rich in uronic acid (Chen et al., 2019; Ding et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…It was also found that polysaccharides form Lycium barbarum were capable of increasing the abundance of Lactobacillus (Ding et al., 2019). The common characteristic of these polysaccharides is that they are rich in uronic acid (Chen et al., 2019; Ding et al., 2019). It was noted that most of the bacteria showed no differences after long‐term intervention of TFPS, unlike observations in cyclophosphamide‐induced mice with disturbed gut microbiota (Chen et al., 2019).…”
Section: Resultsmentioning
confidence: 99%